Territory in Contemporanean Argentinian Poetry: objectivism, 1990’s poetry, and an Antarctic experiment (2020)
Territory, as a special concern for the space in terms of local reality, allows us to reflect on some important novelties surfaced across contemporary Argentinian poetry. The dialogue between common speech and sight that characterize Argentinean 1990’s poetry” (Porrúa 2001, 2004) can be also applied to the analysis of the relationships among subjective perception, changes in the social landscape, and the historical controversies that surround those issues.  El guadal (García Helder) and La zanjita (Desiderio) set the basic frame, and propose territory through observation or experimenting with oral speech. Combined or in separate ways, these possibilities can be found in El cielo de Boedo (Durand), Poesía civil (Raimondi) or Pujato (Cortiñas).Particularly, Raimondi´s and Cortiñas´s books reflect deeply on issues firstly laid out by theArgeninean essay along the 20th century (the function of collective symbols, identity as cultural problem, as well as their connection with the local territory, among other issues).